A multi-purpose hand-tool development: implementation of a collaborative design process in aerospace industry. (5th January 2005) - Kayis, Berman; Hoang, Khoi
In this article, the research associated with the successful development of a new multi-purpose hand tool in the aerospace industry is reviewed. The collaborative design, development and implementation approach using the concept of "real users as active partners" was the key success factor for the high acceptance of the new product among users. A unique application of the group technology concept was used in New Product Development to group similar curvature combinations of the moulds in order to define the type of hand tool proposed to be used. The collaborative design and development process helped create a cultural change in the organisation by increasing the trust and communication between operators, management, and the occupational health and safety department.